Effect of WS2 nanoparticles on the current-voltage characteristics of a polymer solar cell - Rozhkova, X.S.; Aimukhanov, A.K.; Ilyassov, B.R.; Tussupbekova, A.K.; Zeinidenov, A.K.; Alexeev, A.M.; Zhakanova, A.M. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
The paper presents the results of studies of the effect of tungsten disulfide nanoparticles on the optical and electrotransport characteristics of PEDOT: PSS thin films in polymer solar cells. Tungsten disulfide (WS2) nanoparticles were obtained by laser ablation in isopropyl alcohol. The average size of nanoparticles were determined by dynamic light scattering and is ~38 nm. The concentration of WS2 nanoparticles in the solution was calculated based on the density of the WS2 substance. The absorption spectrum of nanoparticles in isopropyl alcohol has been measured. Two bands are observed in 500-900 nm regions, which are associated with direct exciton transitions A1 and B1 in two-dimensional transition metal dichalcogenides with 2H phase. WS2 nanoparticles were added in PEDOT: PSS solution and thin films were deposited from the prepared solution by spin-coating. PEDOT: PSS thin films doped with WS2 were studied by atomic force microscopy (AFM). The arithmetic mean deviation of the surface roughness (Ra) was estimated. Doping with WS2 nanoparticles leads to the increase in Ra of PEDOT: PSS thin films. The optical absorption spectra of doped films have been measured. Also, doping PEDOT: PSS with WS2 nanoparticles results in a long-wavelength shift of the PEDOT absorption maximum. The optimal concentration of WS2 nanoparticles for the preparation of doped PEDOT: PSS thin films is determined, at which the film resistance decreases by almost 2 times, the recombination resistance of charge carriers increases by 4.7 times, and the efficiency of the polymer solar cell increases to 1.94 %.
WS2 нанобөлшектерінің полимерлі күн элементінің вольт-амперлік сипаттамаларына әсері
Влияние наночастиц WS2 на вольт-амперные характеристики полимерного солнечного элемента
Keywords: PEDOT: PSS; WS2 nanoparticles; hole-transport layer; surface morphology; absorption spectra; impedance spectroscopy; organic solar cell; volt-ampere characteristics